Inclusivity in Jepin and Raddat Dance: Exploring Changes in Gender Roles in Traditional Performing Arts - Tindarika, Regaria; Rianto, Ridho; Satrianingsih, Aline Rizky Oktaviari; Aditya, Mega Cantik Putri (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to examine the changes in gender roles in the Jepin dance in Sambas Regency, particularly regarding the involvement of women in performances that were previously dominated by men. The research also aims to understand the impact of these changes on the preservation of art, aesthetics, and the cultural values of the Sambas community. The methodology used is a qualitative approach with literature analysis and in-depth interviews with dance practitioners, cultural actors, and community leaders. The data obtained is then analyzed using anthropological and feminist approaches to explore the dynamics of gender roles in the context of traditional arts. The results show that gender roles in the Jepin dance were initially influenced by social structures and cultural values that restricted women's participation in dance. However, with social development, education, and globalization, women began to be accepted as part of the Jepin dance performances. Women's involvement not only enriched the aesthetics of the dance but also reflected broader social changes in gender equality. The positive impacts of these changes include the preservation of the art and the introduction of new aesthetics, while the negative impacts include potential cultural conflicts regarding violations of traditional norms. Overall, this study demonstrates that the transformation of gender roles in Jepin dance contributes to social change without eliminating the cultural essence embedded in the dance.